EVIDENCE AND FREQUENCY OF NEWLY DIAGNOSED DIABETES MELLITUS IN THE PATIENTS ADMITTED WITH COVID-19 INFECTION - AHMED , M; TARIQ , UB; AHSAN , S; AROOJ , T; SHABBIR , H; BAIG , ZL (Biological and Clinical Sciences Research Journal, 2023)
To find out how often individuals with covid-19 infection develop new cases of diabetes mellitus. The study was conducted at Mirpur Azad Jammu and Kashmir Teaching Hospital, Divisional Headquarter of the Department of Medicine, from January 2021 to June 2021. Adult patients between 18 and 70, regardless of gender, who were diagnosed with the virus showing mild to moderate symptoms determined by RT-PCR test and were not previously reported with diabetes met the inclusion criteria. Within 24 hours of admission, 5cc of each patient’s blood was drawn and sent for testing to determine the BSF, BSR, and HBA1C levels before commencing steroids. Data obtained were analyzed by using (SPSS) version 24.0. Total 130 patients of covid-19 were included who met the inclusion criteria. Mean age of patients was 39.60+ 9.76 years. There were 108 (83.1%) males and 22 (16.9%) females.Twenty-six patients (20%) were diagnosed with DM during admission. The mean age of patients in non-diabetic group was 39.75+ 9.5 years, while in diabetic group it was 51.38+ 12.74 years which was statistically significant (0.001). 24 (92.3%) patients with newly diagnosed DM had HBA1C levels of more than 6.5 which was statistically significant (0.001).We conclude that newly diagnosed DM significantly relates to covid-19 infection. Elderly patients already in pre-diabetic state with increased HBA1C levels are more prone to develop DM after this viral infection.